An Analysis of Emotional Classification in the Characters of “Hello, Goodbye, and Everything in Between” (2022): A Psychological Approach - Ruth Angelina Rehmalemna; Robby Satria (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study explores the emotional experiences of the main characters in the film Hello Goodbye and Everything in Between (2022) by applying David Krech’s theory of emotion classification. The central question of this research is how Krech’s emotional categories appear in the characters and how these emotions shape the psychological dimension of the storyline. The aim is to identify the emotions expressed by the characters and to describe how these emotions influence their conflicts their decisions and the progression of their relationship. This research adopts a qualitative descriptive approach. The data were gathered through close observation of the film by examining key scenes and dialogues and by organizing the emotional expressions according to Krech’s framework. The findings indicate the seven emotional categories proposed by Krech namely guilt, suppressed guilt, self punishment, sadness, shame, hatred and love are present throughout the film. The study contributes to psychological and literary analysis by showing that Krech’s theory offers a useful lens for understanding the emotional depth of fictional characters and provides insight into the motivations and internal struggles that drive the narrative.